2002
DOI: 10.1007/s003830200013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sialadenitis with pleomorphic adenoma of the parotid: coincidental or causal?

Abstract: A 12-year-old boy with a pleomorphic adenoma of the parotid is reported. The excised gland specimen also showed evidence of chronic sialadenitis. The co-existence of these two entities has not been previously reported in the literature surveyed by us. The authors feel that the two conditions may have a common underlying etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Two cases of chronic nongranulomatous sialadenitis alongside salivary pleomorphic adenomas have been reported, the authors suggesting that chronic sialadenitis may result in progressive sialectasis (with stasis and acinar destruction), and that this inflammation later leads to development of neoplasia. 4,5 A recent histological study of 40 major and minor salivary glands identified areas of inflammation in the peritumoral area, pseudocapsule, and in the connective tissue stroma in 95% of the examined specimens. 6…”
Section: Discussionmentioning
confidence: 99%
“…Two cases of chronic nongranulomatous sialadenitis alongside salivary pleomorphic adenomas have been reported, the authors suggesting that chronic sialadenitis may result in progressive sialectasis (with stasis and acinar destruction), and that this inflammation later leads to development of neoplasia. 4,5 A recent histological study of 40 major and minor salivary glands identified areas of inflammation in the peritumoral area, pseudocapsule, and in the connective tissue stroma in 95% of the examined specimens. 6…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the long standing presence of a Warthin tumor may give rise to chronic obstructive sialadenitis in the surrounding gland. [21][22][23] Long standing chronic sialadenitis can give rise to ductal metaplasia, then dysplasia, followed by carcinoma. 24,25 Warthin tumor is boggy on physical examination because of fluid filled cystic spaces.…”
Section: Synchronous Ipsilateral Warthin Tumormentioning
confidence: 99%